The Impact of the Economic Sectors Activity Diversification On the Economic Growth in Iraq During the Period (1980 - 2017) - Sabr, Soud; Saed, Shvan (The Arab Journal of Administration, 2021)
The strategy of economic diversification is an effective strategy that contributes to the economic growth by increasing the contribution of the non-oil producing sectors to the GDP. This is an extreme need for the oil economies, which suffer from structural imbalances and weak production base due to the heavy dependence on oil, which is one of the unlimited resources which is characterized by fluctuations in prices in the international oil markets. Given the fact that the Iraqi’s economy has many natural resources and its GDP is one of the economies which is dominated by its oil sector, it is necessary to adopt effective economic policies to diversify their production base and sources of income, achieving sustainable development and facing external shocks. The purpose of this paper is to measure the contribution of the main sectors on the economic growth in Iraq during (1980-2017) through a theoretical and an empirical part. The theoretical part focuses on economic diversifications through illustrating the concept, definition, importance, purpose and the effect of diversification on the economic growth. On the other hand, the empirical part illustrates the effect of most of the effective sectors on the gross domestic product of Iraq namely, agricultural sector, manufacturing industries sector, other types of mining sector, tourism sector, and crude oil sector. The results of the empirical model showed that it seems that all sectors have a positive effect on the GDP of Iraq, but the effect of all the variables except the oil sector were not notable. Which it had a high effect with regard to other sectors. This proves that there is dominance of oil sector on the economy of Iraq. Finally, In the light of the results obtained in the present study, it seems that one of the most important recommendations might be amending the method of managing oil revenues and how to distribute them between operating and investment spending with a focus on diversification in the latter. Furthermore, Since the oil sector is one of the most influential sectors of GDP, revenues from this sector can be used for the development of other economic sectors, and other outputs from the oil sector can be used in various industries such as petrochemical, plastics, etc., and thus, growth can be achieved in other sectors and in GDP.